Equity Financing, Debt Financing, and Financial Performance in Islamic Banks - Heri Sudarsono; Jannahar Saddam Ash Shiddiqi (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2021)
This research aims to determine the eﬀect of bank size (SIZE), proﬁtability (ROA), eﬃciency (EFF), non-performing ﬁnance (NPF), interest (INTR), and inﬂation (INFL) on proﬁt and loss sharing (PLS) ﬁnancing (equity ﬁnancing), and sale-purchase (SP) ﬁnancing (debt ﬁnancing) Islamic banks in Indonesia. Furthermore, monthly Islamic bank data in June 2014 to July 2020 was used. The autoregressive distributed lag (ARDL) method was used to determine the short and long-term eﬀects of the independent variables on the ﬁnancing variable. The results showed that ROA and EFF have a positive eﬀect on MRF but ROA and EFF have a negative eﬀect on MDA and MSF. NPF has a positive eﬀect on MDF, but has a negative eﬀect on MRF. Meanwhile, SIZE has a negative eﬀect on MDF, MDA, MRF, and MRA. The INTR has a negative eﬀect on MDA, MRF, and MRA. The implication of this research is that ﬁnancialperformance has more inﬂuence on debt ﬁnancing compared to equity ﬁnancing of Islamic banks in Indonesia.